2014
DOI: 10.1001/jamaophthalmol.2014.2876
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum Ferritin and Glaucoma in the South Korean Population

Abstract: laucoma is an optic neuropathy with retinal ganglion cell loss and structural alteration of the optic nerve head, accompanied by progressive vision loss. Glaucomatous disease is the leading cause of irreversible blindness worldwide 1 and a growing public health concern because of an aging worldwide population. 2 Elucidation of risk factors associated with disease pathogenesis may help prevent the resulting disability.Previously identified important risk factors for the development of glaucoma include greater i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 37 publications
(51 reference statements)
4
33
0
Order By: Relevance
“…To our knowledge, only one study1 has demonstrated this relationship, while a few other studies17 18 have suggested that this relationship might be important. Herein, we measure the strength of the association between serum ferritin levels and glaucoma development and explain how this relationship influences glaucoma pathogenesis.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…To our knowledge, only one study1 has demonstrated this relationship, while a few other studies17 18 have suggested that this relationship might be important. Herein, we measure the strength of the association between serum ferritin levels and glaucoma development and explain how this relationship influences glaucoma pathogenesis.…”
Section: Introductionmentioning
confidence: 90%
“…The χ 2 test, Student's t test or Mann–Whitney U test was used to compare demographic characteristics. To evaluate the effects of systemic factors on glaucoma prevalence, we categorised serum ferritin level, serum iron level, serum total iron-binding capacity (TIBC) level, serum transferrin saturation level, serum white blood cell (WBC) level and serum high-sensitivity C-reactive protein (HsCRP) level into quartiles,1 19 21 while serum total vitamin D level was categorised into quintiles 22. Multivariate logistic regression models were constructed to assess possible associations between elevated glaucoma risk and systemic factors that revealed p<0.2 in univariate analysis 23.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17 After an ophthalmology-focused interview, participants underwent visual acuity measurements, automated refraction, slit lamp examination, intraocular pressure measurement, fundus photography, and, when deemed appropriate, visual field examination.…”
Section: Survey Componentsmentioning
confidence: 99%